APPLICATION AND LIABILITIES ASSETS MANAGEMENT BEHAVIOR AS AN INSTRUMENT FOR BANK - ARINI, SINTRI
Assets And Liabilities Management is a mathematical model that manage the alocation of bank?s assets and liabilities. The primary goal from this Assets and Liabilities Management is to maximize earnings subject to acceptable levels of interest rate and liquidity risk. In this thesis, Assets and Liabilities Management is built based on single- period model. The objective function is formulated to minimize the vari- ance of changes in gain with respect to some constraints, such as: asset?s gap constraint, liability?s gap constraint, average yield constraint, distribution constraint, duration constraint, convexity constraint, dan transaction cost con- straint. Meanwhile, liquidity risk is covered by government?s regulation that obtained by Assets and Liabilities Management. Generally, this thesis explain about Assets and Liabilities Management start from formulate the objective function until apply the Assets and Liabilities Management to data of a bank.